Cryptocurrency as an instrument of terrorist financing - Динту, Валерія Аркадіївна; Динту, В. А.; Дынту, Валерия Аркадиевна; Dyntu, Valeriia A.; Дикий, Олег Вікторович; Дикий, О. В.; Дикий, Олег Викторович; Dykyi, Oleh V.; Dykyj, Oleg (Riga : Izdevniecība “Baltija Publishing”, 2021)
The purpose of the article is to explain the use of cryptocurrency as a terrorist financing tool. This article has emphasized the ways, which terrorists appraise for being a reliable fundraising means and their adoption. Methodology. For the purposes of the study, the methods of scientific abstraction, synthesis, observation, generalization, as well as the method of induction of literature and legal documents were used to determine the features of bitcoin, promoting and preventing its use for terrorism financing. Results. The development of the Internet and electronic devices has radically changed all spheres of human life, including criminal activity. Digitalization has led to the improvement of ordinary crimes and the emergence of new types of crime, which, in principle, cannot exist without special digital electronic devices. Among the first implementers of new technologies were terrorists, who took advantage of digitalization to increase profitability. Thus, terrorists have now significantly increased their attention to cryptocurrency as a digital means of payment, namely Bitcoin. Bitcoin has a number of features that have attracted the attention of criminals as a way to evade responsibility for a crime. In particular, decentralization avoids the need for confirmation by a central authority, and pseudo-anonymity provides a certain level of anonymity. In addition, terrorists are aware that Bitcoin's confidentiality is extremely fragile and needs to be enhanced. The paper analyzes several ways to enhance anonymity, such as software that anonymizes traffic and prevents IP identification, peer-to-peer mixers, centralized mixing services (tumbler), and other approaches. It is worth emphasizing that for the fight against crime, the main issue is the de-anonymization of the Bitcoin owner/user, which allows the identification of the criminal. Currently, law enforcement agencies use direct and indirect de-anonymization, proliferation analysis, quantitative analysis, time analysis, and transactional network analysis, among others, to achieve the above goal, which are discussed in detail in this article. In addition, agencies around the world investigated and uncovered terrorist groups and their financial facilitators. Specifically, on August 13, 2020, the U.S. Department of Justice's Office of Public Affairs announced "the largest cryptocurrency seizure in the context of terrorism in history." To investigate the agenda, the legal documents of those investigations that contain information about the terrorist fund-raising mechanism were examined and analyzed. The legal documents revealed that these investigations used the aforementioned de-anonymization approaches.

Мета статті – пояснити використання криптовалюти як інструменту фінансування тероризму. У цій статті наголошено на способах, які терористи оцінюють як надійний засіб збору коштів та їх застосування. Методологія. Для цілей дослідження були використані методи наукового абстрагування, синтезу, спостереження, узагальнення, а також метод індукції літератури та правових документів для визначення особливостей біткойна, сприяння та запобігання його використанню для фінансування тероризму. Результати. Розвиток Інтернету та електронних пристроїв докорінно змінив усі сфери людського життя, у тому числі й злочинну діяльність. Цифровізація призвела до вдосконалення звичайних злочинів та появи нових видів злочинів, які в принципі не можуть існувати без спеціальних цифрових електронних пристроїв. Серед перших реалізаторів нових технологій були терористи, які скористалися цифровизацією для підвищення прибутковості. Таким чином, зараз терористи значно посилили свою увагу до криптовалюти як до цифрового платіжного засобу, а саме до біткойну. Біткойн має ряд особливостей, які привертають увагу злочинців як спосіб ухилення від відповідальності за злочин. Зокрема, децентралізація дозволяє уникнути необхідності підтвердження з боку центрального органу, а псевдоанонімність забезпечує певний рівень анонімності. Крім того, терористи усвідомлюють, що конфіденційність біткойна надзвичайно крихка і потребує посилення. У статті аналізуються кілька способів підвищення анонімності, наприклад програмне забезпечення, яке анонімізує трафік і запобігає ідентифікації IP, однорангові змішувачі, централізовані служби мікшування (тумблер) та інші підходи. Варто підкреслити, що для боротьби зі злочинністю основним питанням є деанонімізація власника/користувача біткойн, що дозволяє ідентифікувати злочинця. Зараз для досягнення вищезазначеної мети правоохоронні органи використовують пряму та непряму деанонімізацію, аналіз поширення, кількісний аналіз, аналіз часу та аналіз мережі транзакцій, які детально розглянуті в цій статті. Крім того, агентства по всьому світу розслідували та виявляли терористичні групи та їхніх фінансових посередників. Зокрема, 13 серпня 2020 року Управління зі зв’язків з громадськістю Міністерства юстиції США оголосило про «найбільше захоплення криптовалюти в контексті тероризму в історії». Для вивчення порядку денного були досліджені та проаналізовані правові документи тих розслідувань, які містять інформацію про механізм збору коштів тероризму. Правові документи показали, що ці розслідування використовували вищезгадані підходи деанонімізації.
Dyntu V. Cryptocurrency as an instrument of terrorist financing / V. Dyntu, O. Dykyj // Baltic Journal of Economic Studies. - Vol. 7. - No. 5. - Riga : Izdevniecība “Baltija Publishing”, 2021. - P. 67-72.
Keywords: cryptocurrency; Bitcoin; terrorism-financing; criminal investigation; de-anonymization; криптовалюта; біткойн; фінансування тероризму; кримінальне розслідування; деанонімізація; Research Subject Categories::LAW/JURISPRUDENCE